Study on the Penicillin-content of botrytized wines and noble rotted berries in Tokaj-region - Kállay, M.; Bene, Zs. (International Journal of Horticultural Science, 2003)
Favourable parameters are offered to the formation of noble rot caused by Botrytis cinerea by the climatic conditions, soil circumstances and grape-varietes of Tokaj-region. As the result of noble rot, aszú-berries represent the most important raw material of the world-wide known Tokaji Aszú Wine. The objective of this study was to measure the penicillin-content of aszú-berries and Tokaj Wine Specialities. As the result of infection of Botrytis free way can be opened in front of other mould strains, especially Penicillium and Aspergillus. There is a possibility to the presence of Penicillium chrysogenum on the surface of aszú-berries during noble rotting process. P. chrysogenum was found to produce the so called Naturally Derived Penicillins such as Penicillin-V (phenoximethyl-penicillin). According to our findings the Penicillin-V content was detected between 0.4 and 26 mg/1 wine and 0-74 mg/kg aszú-berry. These values do net have therapeutic effect, but physiological benefit and it can be a basis to the qualification of the raw material of Tokaj Wine Specialities naturally together with the other component of noble rotted berries and botrytized wines.